The Search for Magnetotail Twisting at Mercury: Comparing MESSENGER Observations With the Terrestrial Case. Issue 24 (17th December 2022) - Romanelli, N.; DiBraccio, G. A.; Slavin, J.; Bowers, C.; Weber, T.
Abstract: Previous studies reported that the terrestrial and Martian magnetotails can become twisted due to the solar wind‐planetary interaction; however, the associated physical processes proper of intrinsic and induced magnetospheres are still under debate. In particular, there is evidence that the Interplanetary Magnetic Field (IMF) dawn‐dusk component (By) plays a major role in both environments, affecting the sense of twist. Here, we analyze all MErcury, Surface, Space ENvironment, GEochemistry and Ranging Magnetometer observations to investigate the IMF By influence on Mercury's magnetotail. We find that Mercury's tail twist is very small (≲3°), for a median downtail distance of ∼2 Mercury radii. We also identify a correlation between the IMF By and the local By component around the magnetotail current sheet. These results suggest the small (or lack of) twist may be explained by the dipolar field strength in the near‐magnetotail. We examine this hypothesis by putting these observations into context with studies on the terrestrial magnetotail. Plain Language Summary: Previous studies identified a twist in the magnetotail structures on Earth and Mars. This twist is affected by the dawn‐dusk component (By) of the background magnetic field convected by the solar wind. To improve the current understanding of these phenomena, we analyze all MErcury, Surface, Space ENvironment, GEochemistry and Ranging (MESSENGER) magnetic field data in Mercury's magnetotail. We find an upper bound for the tail twist of ∼3°, based on observations obtained centered at ∼2 Mercury radii downstream from the planet. Our results suggest the small (or lack of) twist at Mercury could be understood in terms of the dipolar field strength in the magnetotail region near the planet. We put these observations into context with conclusions reported at the terrestrial magnetotail and argue the Bepi‐Colombo mission may see a more developed twist, as the planned apoapsis is expected to be further downtail from Mercury, compared to MESSENGER. Key Points: We find an upper bound for Mercury's near tail twist of ∼3°, in association with the Interplanetary Magnetic Field (IMF) dawn‐dusk (By) component The IMF By is able to affect Mercury's magnetotail current sheet and the local dipolar field can partly explain the small twist Comparisons with observations from Earth suggest the tail twist could be detectable by Bepi‐Colombo further downstream of Mercury